Strongyloides stercoralis and Organ Transplantation - Bhalaghuru Chokkalingam Mani; Moses Mathur; Heather Clauss; Rene Alvarez; Eman Hamad; Yoshiya Toyoda; Mark Birkenbach; Mustafa Ahmed (Case Reports in Transplantation)
Strongyloides is a parasite that is common in tropical regions. Infection in the immunocompetent host is usually associated with mild gastrointestinal symptoms. However, in immunosuppressed individuals it has been known to cause a “hyperinfection syndrome” with fatal complications. Reactivation of latent infection and rarely transmission from donor organs in transplanted patients have been suggested as possible causes. Our case highlights the importance suspecting Strongyloides in transplant recipients with atypical presentations and demonstrates an incidence of donor derived infection. We also review the challenges associated with making this diagnosis.